2018
DOI: 10.3952/physics.v58i1.3657
|View full text |Cite
|
Sign up to set email alerts
|

Study of surface electric field and photocarrier dynamics in InAs by means of a modified double-pump-pulse terahertz emission method

Abstract: In this study we report the investigation of terahertz (THz) emission efficiency dynamics in p-type InAs using a double-pump-pulse (DPP) THz emission method. We also suggest a novel modification of the standard DPP method which allows us to measure the indirectly modulated THz pulse. The obtained results reveal that the first optical pulse increases the free carrier concentration and enhances the surface electric field. This field prevents perpendicular but improves parallel to the surface electric dipole form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…In the literature, there are several reports of photocarrier lifetime measurements in GaAs [35,54], InAs [35,55], InP [ 35,56], GaAsSb [57], GaInNAs [58], and GaPAsN [59] using OPTP. The photocarrier lifetime ranges from 1 to 5 ps in GaAs to 200-660 ps in InAs to∼1.4 ns in InP NWs [35].…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, there are several reports of photocarrier lifetime measurements in GaAs [35,54], InAs [35,55], InP [ 35,56], GaAsSb [57], GaInNAs [58], and GaPAsN [59] using OPTP. The photocarrier lifetime ranges from 1 to 5 ps in GaAs to 200-660 ps in InAs to∼1.4 ns in InP NWs [35].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the pulse generator employing the AsSe 2 core MOF based MZI device is shown to have some potential applications, e.g. the measurement of indirectly modulated terahertz (THz) pulse [25] and harmonic generation [26].…”
Section: Introductionmentioning
confidence: 99%